Association Between Klotho Gene Polymorphism and Markers of Bone Metabolism in Patients Receiving Maintenance Hemodialysis in Iran (Iranian Journal of Kidney Diseases, 2017)
Introduction. Some genetic variations of Klotho have been reported as a risk factor for calcification and hyperphosphatemia in chronic kidney disease. Klotho polymorphism is also associated with outcome in patients receiving hemodialysis. This study aimed to evaluate the relationship between Klotho single nucleotide polymorphism (SNP) and bone metabolism as an early prognostic measure for chronic kidney disease.   Materials and Methods. Sixty patients receiving hemodialysis and 60 age-matched controls were enrolled in the study of the assessment of 2 types of Klotho polymorphism (G395A and C1818T). Serum biochemical parameters, including calcium, phosphate, urea, creatinine, parathyroid hormone, and 25-hydroxyvitamin D3 were measured.  Results. The frequency of being A carriers suggested marginal significances between the groups (GA and AA, 30% versus GG, 18.3%, P = .06), but such significant results were not found for the T allele carriers (CT and TT, 76.6% versus CC, 76.6%, P > .99). Homozygote and heterozygote individuals for the A allele at G395A SNP (A allele carriers) were more likely to be on hemodialysis (odds ratio, 1.43; 95% confidence interval, 0.60 to 3.30), but this association was not true for T allele carriers of C1818T SNP. Parathyroid hormone and serum calcium, phosphate, creatinine, and urea showed prominently higher levels in the patients receiving hemodialysis compared with control individuals. Conclusions. The A allele of the G395A polymorphism of Klotho, which emerges the higher levels of phosphate, may be associated with the risk of mortality in Iranian patients receiving hemodialysis.